POLA PERKEMBANGAN NORMA DAN SANKSI SUAP DALAM FATWA MAJELIS ULAMA INDONESIA, NAHDLATUL ULAMA DAN MUHAMMADIYAH - Rusdi Sulaiman; Sadulloh Muzammil (Fakultas Syariah (Syari'ah Faculty ), 2021)
This paper, through literature studies and historical and normative approaches, outlines the development of norms and risywah sanctions in the MUI, NU and Muhammadiyah Fatwas after bribery crimes are regulated by positive laws in Indonesia. As far as norms are concerned, the fatwas of the three institutions tend to follow historical patterns, continuing the classical norms of risywah. The construction of bribery norms in the third fatwa is inseparable from the identity they hold, namely the fatwa community that has the right to be protected normatively religiously (halal / haram) and practically. MUI identifies itself as an NGO, not the Mufti of the State, while NU and Muhammadiyah confirm themselves as community organizations. As for the bribery sanctions, the three institutions bring together the interests of the fatwa community and the government, recognize the rights and qualifications of the government to implement ta'zir, and identify themselves as citizens who comply with positive laws.